MENINGKATKAN KOMPETENSI PEDAGOGIK GURU MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) - Kasmi, Kasmi (JURNAL GLOBAL EDUKASI, 2018)
Abstract: Pedagogic competence is the competence possessed by teachers who contribute to the development of curriculum, syllabus, lesson plans, learning and classroom management, carry out active, creative, innovative effective and enjoyable learning, assess students' results, guide students, and develop professionalism as teachers. Tujuna School Action Research is to improve teacher competency in preparing Learning Implementation Plans (RPP). This is motivated by the low competence of teachers in preparing the Learning Implementation Plan (RPP). Based on the results of supervision of the principal. The subjects of this study were 12 teachers of Koto Kampar Hulu Junior High School, totaling 12 people consisting of 2 men and 10 women. This study consisted of 2 cycles. Each cycle consists of 2 meetings. The results of this school action research were successful because it increased from the first cycle to the second cycle, namely the observation of the RPP preparation activities on average 66.87% and rose to 77.56%, while based on supervision of the principal in the first cycle 69.17% and increased in the second cycle to 78.38%. The school supervisor's academic supervision actions can improve the pedagogics of guri in preparing lesson plans at Koto Kampar Hulu 3 Public Middle School. Keywords: Teacher's Pedagogic Competence, RPP Abstrak: Kompetensi pedagogik merupakan kompetensi yang dimiliki oleh guru yang berkontribusi dalam pengembangan kurikulum, silabus, RPP, manajemen pembelajaran dan kelas, melaksanakan pembelajaran yang aktif, kreatif, inovatif efektif dan menyenangkan, menilai hasil peserta didik, membimbing peserta didik, serta mengembnagkan profesionlisme sebagai guru. Tujuna Penelitian Tindakan Sekolah ini adalah untuk meningkatkan kompetensi guru dalam menyusun Rencana Pelaksanaan Pembelajaran (RPP). Hal ini dilatarbelakangi oleh rendahnya kompetensi guru dalam menyusun Rencana Pelaksanaan Pembelajaran (RPP). Berdasakan hasil supervisi kepala sekolah. Subjek penelitian ini adalah guru SMPN 3 Koto Kampar Hulu yang berjumlah 12 orang terdiri dari 2 orang laki-laki dan 10 orang peremuan. Penelitian ini terdiri dari 2 siklus. Setiap siklus terdri dari 2 kali pertemuan. Hasil penelitian dari penelitian tindakan sekolah ini berhasil karena meningkat dari siklus I ke siklus II, yaitu pada pengamatan aktivitas penyusunan RPP rata-rata 66,87% dan naik menjadi 77,56%, sedangkan berdasarkan supervise kepala sekolah pada siklus I 69,17% dan meningkat pada siklus II menjadi 78,38%. Tindakan supervisi akademik kepala sekolah dapat meningkatkan pedagogik guri dalam menyusun RPP di SMPN 3 Koto Kampar Hulu. Kata kunci: Kompetensi Pedagogik Guru, RPP